2014
DOI: 10.1002/adma.201402797
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Star Copolymer‐Based Bimodal Fluorogenic/Magnetic Resonance Probes for Concomitant Bacteria Detection and Inhibition

Abstract: Four-arm star-shaped copolymers, TPE-star-P(DMA-co-BMA-co-Gd), containing TPE cores with an aggregation-induced emission (AIE) feature, a T 1 -type magnetic resonance (MR) contrast agent, and amphiphilic cationic arms, are synthesized. By taking advantage of non-covalent interactions between star copolymers and bacteria surfaces, bimodal fluorometric/MR detection and concomitant inhibition of both Gram-positive and Gram-negative bacteria strains in aqueous media are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 71 publications
0
103
0
Order By: Relevance
“…The different binding affinities of certain cationic polymers for disease-causing bacteria have recently been exploited to detect pathogens [41][42][43][44] or to discriminate between Gram-positive and Gram-negative bacteria and fungi [45]. It has been suggested that negative charges arising from teichoic acids are responsible for the higher binding of polycations with Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The different binding affinities of certain cationic polymers for disease-causing bacteria have recently been exploited to detect pathogens [41][42][43][44] or to discriminate between Gram-positive and Gram-negative bacteria and fungi [45]. It has been suggested that negative charges arising from teichoic acids are responsible for the higher binding of polycations with Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a special fluorescent system with aggregation‐induced emission (AIE) characteristic has been discovered by Tang's group and widely applied to various biomedical fields . Up to now, All MRI probes used in AIE‐based dual‐mode imaging are Gd chelates, a T 1 contrast agent . Although Gd chelates dominate the main market of MRI contrast agents, the U.S. Food and Drug Administration (FDA) has given the highest black box warning of this agent for causing nephrogenic systemic fibrosis in patients with kidney disfunctions .…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic block copolymers have been attracting attention for years due to their ability to form different types of self‐assemblies in aqueous environment which find use in biomedical applications, for example, drug carriers, sensors, fluorogenic nanostructures and vehicles for the transportation of biological molecules such as DNA, RNA, and proteins . Among polymer nanostructures such as micelles, nanocapsules, polymersomes, block copolymer micelles (BCMs) come into prominence due to enhanced permeability and retention (EPR) effect, small particle size, high loading capacity, prolonged circulation, and accumulation in the required pathological site(s) in the body …”
Section: Introductionmentioning
confidence: 99%